A new proposal in the approach of vulvovaginitis - Campaner, Adriana Bittencourt; Carvalho, Newton Sergio de; Eleutério, José (Brazilian Journal of Sexually Transmitted Diseases, 2023)
The authors report on a recently published review article on the approach to vulvovaginitis through flowcharts, taking into account the peculiarities of each service, according to the diagnostic methods that are available.